Kolaborasi Lembaga Mitra dalam Advokasi Akses Ketersediaan Obat bagi Orang dengan Disabilitas Psikososial di Perhimpunan Jiwa Sehat Indonesia - Dian Fitriani; Sokhivah Sokhivah (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2024)
Access to mental healthcare, especially psychopharmacological treatment, for people with psychosocial disabilities (ODDP) remains a significant challenge in Indonesia. Discrepancies between regulations and their implementation, coupled with limited availability of psychiatric medications, pose major obstacles. This research analyzes the collaborative efforts of the Mental Health Association (PJS) and its strategic partners in advocating for increased access to medication for ODDP. The research focuses on the stages of advocacy, the roles of each partner, the collaboration process, and the outcomes of these advocacy efforts. Employing a qualitative approach, this research involved in-depth interviews with PJS officials to explore the roles of partner institutions in advocacy. The findings reveal that PJS has systematically engaged in advocacy, collaborating with various strategic partners such as BPJS Watch, WHO Indonesia, and PDSKJI. This collaborative effort has proven effective in identifying issues, formulating solutions, and driving policy changes. However, challenges such as limited resources and the complexity of the issues persist. The research concludes that collaboration among partner institutions is key to improving access to medication, particularly psychiatric medications, for ODDP. Sustained and measurable advocacy is necessary to ensure that ODDP can obtain equitable and accessible quality mental health services.